Effectiveness of Strict Adherence to Ergonomic Advice on Quality of Work in Sugarcane Workers - Wandre, Shreya Shivaji; Patil, Pragati (Journal of Neonatal Surgery, 2025)
Introduction: The workers in this field often face tough physical challenges, such as repeating the same motions, working in uncomfortable positions and using heavy tools. These demands can put a strain on their bodies and lead to musculoskeletal disorders (MSDs) which are major cause of work related injuries and pain. Regular adherence to ergonomic advice, including the use of ergonomically designed tools and the adoption of safe work practices is necessary in reducing the MSDs among sugarcane workers. Therefore, strict adherence to ergonomic principles is essential for improving both the health outcomes and work performance of sugarcane workers. Aim: To study the effectiveness of strict adherence to ergonomic advice on quality of work in sugarcane workers. Methodology: Distribution of data collection sheets was done to 41 participants in Karad city. Descriptive data regarding the effectiveness of strict adherence to ergonomic advice on quality of work in sugarcane workers were collected. Result: A total of 41 responses were collected. The participants included were between the age group 18 to 60 years. Both males and females were included. Before the intervention, almost 98% of workers felt that their musculoskeletal pain negatively affected their work performance. However, after the intervention, the situation improved dramatically. Conclusion: Sugarcane harvesting presents considerable ergonomic challenges, leading to a high incidence of musculoskeletal disorders among workers. By promoting strict adherence to ergonomic principles, it is possible to reduce these risks and enhance the quality of work.